Uncertainties of mothers of children in conservative renal treatment - Fernanda Lise; Eda Schwartz; Viviane Marten Milbrath; Diana Cristiano Castelblanco; Margareth Angelo; Raquel Pötter Garcia (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To understand the uncertainties of mothers of children undergoing conservative renal treatment due to the child's illness. Method: A qualitative study was carried out with 11 mothers of children undergoing conservative renal treatment at a pediatric nephrology service in the southern region of Brazil. For the data collection, a semi-structured interview and conventional content analysis were performed. Results: Two categories of statements emerged: "Uncertainties regarding the disease and adaptation methods" and "Experiencing unpredictability". The uncertainties were due to the ambiguity of the symptoms and reasons for the development of the disease, lack of information, clarity and unpredictability in relation to the future. Conclusion and implications for practice: Faced with uncertainties, mothers seek to maintain emotional balance, but need support from the healthcare team and nursing team, in primary health care, in order to promote , assurance by giving clear information on how this process occurs, reducing anxiety regarding the unpredictability of the disease in the future.